2009
DOI: 10.1590/s0004-28032009000300013
|View full text |Cite
|
Sign up to set email alerts
|

Could gastric histology be a useful marker for making decision on Helicobacter pylori eradication therapy in patients with dyspepsia?

Abstract: Since upper gastrointestinal endoscopy is part of the functional dyspepsia investigation and serology for anti-CagA antibody is not available in daily clinical practice, by biopsying gastric mucosa we would only be able to selectively apply H. pylori eradication therapy for those with histology that best correlate with virulent infecting strains (moderate or severe gastritis)--around (1/4) of our study patients with dyspepsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
3
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
4
3
0
1
Order By: Relevance
“…29 In the present study, intestinal metaplasia was seen in 4 (3.9%) patients of non ulcer dyspepsia on gastric biopsy and was also of mild grade. This is in concordance with other studies which reported intestinal metaplasia in 2.5% 19 and 8% 21 NUD patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…29 In the present study, intestinal metaplasia was seen in 4 (3.9%) patients of non ulcer dyspepsia on gastric biopsy and was also of mild grade. This is in concordance with other studies which reported intestinal metaplasia in 2.5% 19 and 8% 21 NUD patients.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with other studies where histopathological features of gastritis was observed in the range of 70-92% in patients with NUD. [18][19][20] Chronic gastritis alone was seen in 21(20.5%) patients, both acute and chronic gastritis in 63 (61.7%) and 18 (17.6%) patients had normal mucosal biopsies in the present study.…”
Section: Discussionmentioning
confidence: 59%
“…This result was in agreement with observations by Nwokediuko and Okafor, 17 who found that only 29.3% of patients with functional dyspepsia had normal histology of gastric biopsies by histological examination. This result is also in accordance with which was reported by Arruda et al, 18 who studied 40 dyspeptic patients (28 women and 12 men) with endoscopically normal stomach and found 72.5% of patients with gastritis by histological examination. This emphasizes the role of biopsy in examining a case of dyspepsia as the normal endoscopy does not rule out underlying pathology.…”
Section: Discussionsupporting
confidence: 93%
“…The intensity of lesions observed by histology has also been proposed as a criterion to select dyspeptic patients to be treated by eradication therapy. According to this criterion, one-quarter of the dyspeptic patients with moderate to severe gastritis would be treated in Brazil [15].…”
Section: Histologymentioning
confidence: 99%